P67-F rsEEG markers in subjects with MCI due to Alzheimer's disease (ADMCI) and interictal epileptiform discharge. Issue 7 (July 2019) - Lizio, Roberta; Babiloni, Claudio; Bonaventura, Carlo Di; Noce, Giuseppe; Pascarelli, Maria Teresa; Eldellaa, Dott. Ali; Soricelli, Andrea; Ferri, Raffaele; Nobili, Flavio; Famà, Francesco; Limatola, Cristina; Palma, Eleonora; et al.
Abstract : Background: It is well-known that compared to normal elderly (Nold) subjects, patients with dementia due to Alzheimer's disease (ADD) manifest ten times convulsive seizures. The present study tested the different features of the resting state eyes-closed electroencephalographic (rsEEG) rhythms in a group of patients with mild cognitive impairment due to AD and interictal epileptiform discharge (ADMCI IED+), compared to groups of ADMCI patients without interictal epileptiform discharge (ADMCI IED−), ADD patients, and Nold subjects. Methods: Clinical, neuropsychological, and rsEEG data, in 30 Nold, 31 ADMCI IED−, 11 ADMCI IED+, and 30 ADD subjects were available in an international archive. Individual alpha frequency peak was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were considered. eLORETA estimated the rsEEG cortical sources in EEG segments free from artifacts and IED. The analysis of the area under the receiver operating characteristic (AUROC) curve computed the classification rate. Results: Compared to the Nold group, the ADMCI IED−, ADMCI IED+ and ADD groups presented higher widespread delta source activities and lower posterior alpha source activities. As novel EEG results, compared to the ADMCI IED- group, the ADMCI IED+ unveiled higher frontal and temporal delta source activities. Furthermore, temporal delta source activity allowed a good classification (AUROC > 0.85) between the ADMCI IED− and ADMCI IED+ individuals. Conclusions: In quiet wakefulness, the abnormalities in cortical neural synchronization underpinning brain arousal at delta frequencies are higher in the ADMCI IED+ than the ADMCI IED− subjects.